Diagnosing and treating fatty liver disease: strategies for hepatocellular carcinoma and cardiovascular disease prevention - Ishikawa, Toru (Clinical and Experimental Hepatology, 2025)
The link between lifestyle-related conditions and fatty liver disease has attracted considerable attention in recent years. The number of patients with metabolic dysfunction-associated steatotic liver disease (MASLD), often co-occurring with obesity, diabetes, and dyslipidemia, continues to rise. Accumulating evidence suggests that these conditions synergistically increase the risk of progression to cirrhosis and hepatocellular carcinoma (HCC). Consequently, there is a growing need for testing to identify high-risk liver disease patients based on lifestylerelated conditions, distinct from chronic viral hepatitis or alcohol-induced liver disease, and to determine the most appropriate treatments for these conditions, especially obesity, diabetes, and dyslipidemia. This review outlines the strategy for treating fatty liver disease currently being used in community hospitals, with the goal of reducing HCC and preventing cardiovascular disease.